Efficiency of transcatheter aortic valve implantation in patients with high surgical risk: long-term results of a single-center prospective study - O. V. Kamenskaya; I. Yu. Loginova; E. I. Kretov; A. A. Prokhorikhin; A. R. Tarkova; V. I. Baystrukov; V. V. Lomivorotov; A. M. Karaskov (Российский кардиологический журнал)
Aim. To study long-term results and predictors of adverse outcomes of transcatheter aortic valve implantation in patients with high surgical risk with severe aortic stenosis.Material and methods. The prospective single-center study included 140 patients with hemodynamically relevant aortic stenosis who underwent transcatheter aortic valve implantation. We assessed hemodynamic and clinical status, quality of life before and after 1 year of the intervention.Results. In the long-term follow-up after transcatheter aortic valve implantation, an improvement in the quality of life was noted in both the physical and psychoemotional aspects of health. We did not registered cases of prosthesis dysfunction, repeated surgical interventions one-year survival was 92%. Predictors of adverse outcomes of aortic valve transcatheter implantation were the comorbidity index (odds ratio (OR) 2,8 (1,6-4,9), p<0,001) and, especially, the comorbidity index over 5 points (OR 9,3 (2,9-19,4), p<0,001). Initially low level of quality of life, both in the physical aspect (OR 0,93 (0,86-0,99), p=0,013) and in the psycho-emotional aspect of health (OR 0,94 (0,89-0,99), p=0,027).Conclusion. Aortic valve transcatheter implantation showed high efficiency in improving the quality of life and reducing mortality in patients with severe aortic stenosis and high surgical risk. Initially low level of quality of life and comorbidity index adversely affect on long-term results.